ANALISIS PENERAPAN PSAK 102 ATAS PEMBIAYAAN MURABAHAH (STUDI KASUS PADA BANK MANDIRI SYARIAH) - Putri Eka Wardani (e_Jurnal Ilmiah Riset Akuntansi, 2017)
This study aims to determine the process of murabahah financing at PT. Bank Syariah Mandiri, such as the accounting treatment and its compliance with financial accounting standards (psak) 102. Methods in this study using descriptive qualitative and the results of this study showed that in terms of recognition and measurement PT. Bank Syariah Mandiri is in conformity with PSAK 55 "financial instrument: recognition and measurement" and in terms of presentation of PT. Bank Syariah Mandiri is in accordance with psak 50 "financial instrument: presentation". But in terms of disclosure PT. Bank Syariah Mandiri is not in accordance with PSAK 60 "financial instrument: disclosure" Because PT. Bank Syariah Mandiri applies two contracts in one transaction. Overall PT. Bank Syariah Mandiri has complied with PSAK 102 revision 2013 in performing murabahah financing.